Pré-eclâmpsia e risco de alterações no ultrassom de crânio de recém-nascidos prematuros - Giacóia, Glauce Regina Fernandes [UNESP] (2015)
Background: Preeclampsia (PE) is the most common medical complication in pregnancy, however data on the morbidity and outcome for preterm infants of preeclamptic mothers are conflicting, and few studies address this issue. Objective: To determine the prevalence of cranial ultrasound abnormalities and to identify variables that affect the risk of these abnormalities in very low birthweight infants (VLBW) from preeclamptic and normotensive mothers. To investigate the influence of intrauterine growth restriction on the cerebral ultrasound findings. Methods: A cohort of all inborn VLBW infants admitted to NICU at University Hospital-Botucatu School of Medicine-UNESP from January 2009 to December 2013. Infants who was not assessed by cranial ultrasound screening were excluded. Two groups of infants: 1: Preeclamptic mothers (PE) and 2: Normotensive mothers were compared regarding gestational and neonatal data. Primary outcome: cranial ultrasound abnormalities (intraventricular hemorrhage grades I to IV and periventricular leukomalacia). Logist regression analyses were used to identify risk factors for ultrasound abnormalities. Results: A total of 381 VLBW infants were studied, 151 born to preeclamptic mothers and 230 from normotensives. The prevalence of abnormal ultrasound findings was 39%, with lower rate in PE group (30% vs 45%; p=0,007). In PE group the gestational age was higher, intrauterine growth restriction was very common and neonatal morbidity was lower. PE was not an independent risk or protective factor for cranial ultrasound abnormalities on logistic regression analysis. Antenatal magnesium sulphate therapy, chorioamnionitis and intrauterine growth restriction were not associated with ultrasound findings. Gestational age and cesarean delivery were protective factors, whereas surfactant administration, inotropic use within the first 72 hours of life, and neonatal infection were associated with increased risk of cranial ultrasound ...